Prevalence and Burden of Primary Headache Disorders in Kuwaiti Children and Adolescents: A Community Based Study - Al-Hashel, Jasem Yousef; Ahmed, Samar Farouk; Alroughani, Raed (Frontiers in Neurology, 2019)
Background/Objective: Primary headaches are common in the pediatric and adolescent population and can be disabling for them and their families. We aimed to assess the prevalence and burden of primary headache disorders among children and adolescents in Kuwait. Methods: A cross-sectional community-based study included Kuwaiti population aged 6–17 years. They were randomly recruited from all six governorates of Kuwait using stratified multistage cluster sampling. The Headache-Attributed Restriction, Disability, and Social Handicap and Impaired Participation (HARDSHIP) questionnaire for children and adolescents was used to collect the data. Results: Data were collected from 3,423 subjects; 664 subjects were diagnosed as having primary headache disorders. The mean age was 12.61 ± 2.51 years and 64.2% were females. One year prevalence of headache was 19.4%. It was significantly prevalent in females compared to males (25.2% vs. 13.8%; P < 0.001). Primary headache disorder significantly increased in age group 12–17 when compared to age group 6–11 years (25.8% vs. 10.4 %; p < 0.001). One year primary headache prevalence showed non-significant differences in both males and females in age group 6–11 years (10.1% in males vs. 10.6% in females; P < 0.79), while it was significantly higher in female vs. males (38.1% vs. 15.8%; P < 0.001) in age group 12–17 years. Migraine prevalence was 10.9% followed by tension type headache (TTH) 6.2% and chronic headache 0.9%. Medical care utilization was reported in 67% of our cohort. The majority (95%) of the patients received symptomatic drugs for headache attacks and only 7.5% used preventive medication. The students with headache lost a mean of 1.29 ± 1.23 days of school, reported mean of 1.16 ± 1.50 days they could not do activities they had wanted to. Their parents lost a mean of 1.01 ± 1.02 days of work because of headaches of their children during the preceding 4 weeks of the study. Conclusions: The estimated 1 year prevalence of headache was 19.4% overall. Primary headache prevalence increased with age and it was more prevalent in female adolescents compared to males of the same age. Headache disorders in children/adolescents affect school and social activities as well as their parents work. The awareness for early diagnosis and preventive medications for headache in this age group may reduce the headache burden.